1986
DOI: 10.1111/j.1348-0421.1986.tb02971.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infections of Dogs with Type C Influenza Virus

Abstract: A study was performed to determine if type C influenza infection could be established in dogs as a model for human cases. Mongrel dogs were infected with the Ann Arbor/1/50 strain of type C influenza virus and were examined for clinical symptoms, virus isolation and antibody response. After the first exposure to the virus, all infected animals developed nasal discharge and some of them also showed swelling of the eyelids, and suffusion of the eyes with tears and eye mucus, within 1 to 4 days. The animals showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Furthermore, human influenza C virus isolates were found to be closely related to pig isolates, suggesting that interspecies transmission of influenza C virus between humans and pigs has occurred in nature (24). Influenza C virus-specific antibodies were also detected in dogs (26,27,39), but detection or isolation of the virus from this animal species has not been documented, although experimental infection resulted in clinical symptoms and viral replication (38). Consequently, influenza C viruses are not restricted to humans, but the potential role of pigs or dogs as an animal reservoir for human influenza C virus remains to be elucidated.…”
mentioning
confidence: 98%
“…Furthermore, human influenza C virus isolates were found to be closely related to pig isolates, suggesting that interspecies transmission of influenza C virus between humans and pigs has occurred in nature (24). Influenza C virus-specific antibodies were also detected in dogs (26,27,39), but detection or isolation of the virus from this animal species has not been documented, although experimental infection resulted in clinical symptoms and viral replication (38). Consequently, influenza C viruses are not restricted to humans, but the potential role of pigs or dogs as an animal reservoir for human influenza C virus remains to be elucidated.…”
mentioning
confidence: 98%
“…Apparently, influenza C virus cannot be included in this category. It has been suggested, however, that recurrent infection with influenza C virus occurs frequently, even soon after primary infection (6,9,12). It is likely that reinfection occurred in Kadaklan as well since the HI titers were maintained at relatively high levels up to late in life (see Fig.…”
mentioning
confidence: 99%
“…Additionally, Ohwada et al (13) showed that mongrel dogs could be repeatedly infected with influenza C virus, developing nasal discharge after each exposure to the virus. However, virus growth in the nose seemed to be suppressed considerably in the reinfected dogs since virus was isolated less frequently in the second and third infections than in the first one.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of Minuse et al (9) showed that no characteristic symptoms were produced in ferrets, hamsters, and monkeys inoculated intranasally with influenza C virus though the virus was recovered from the nasal turbinates and the animals developed serum HI antibodies. In contrast, pigs and dogs were shown to develop clinical symptoms characterized by difficulties in breathing (pigs) and increased nasal secretions (pigs and dogs) (2,13). Based on the studies on an outbreak of influenza C unassociated with other respiratory infections.…”
Section: Discussionmentioning
confidence: 99%